2005
DOI: 10.1177/08830738050200110601
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Topiramate in Refractory Epilepsy of Childhood

Abstract: This study aimed to evaluate the long-term efficacy and safety of topiramate in treating children with drug-resistant epilepsy. A multicentric, retrospective, open-label, add-on study was undertaken of 277 children (mean age 8.4 years; range 12 months to 16 years) affected by drug-resistant epilepsy. The efficacy was rated according to the seizure types and epilepsy syndrome. After a mean period of 27.5 months of treatment (range 24-61 months), 11 patients (4%) were seizure free and 56 (20%) had more than 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 36 publications
0
29
1
1
Order By: Relevance
“…[249,[251][252][253] Expressive language, attention, memory, processing speed, arithmetic and spatiotemporal skills may also be affected. [237,239,245] Language problems, more common in adults, include word-finding and speech fluency problems. [230,234] Risk factors for language problems may include simple partial seizures, a left temporal EEG epileptic focus and a history of cognitive problems.…”
Section: Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…[249,[251][252][253] Expressive language, attention, memory, processing speed, arithmetic and spatiotemporal skills may also be affected. [237,239,245] Language problems, more common in adults, include word-finding and speech fluency problems. [230,234] Risk factors for language problems may include simple partial seizures, a left temporal EEG epileptic focus and a history of cognitive problems.…”
Section: Cnsmentioning
confidence: 99%
“…[230][231][232][233][234][235][236][237][238][239][240][241][242][243][244][245][246][247] Psychomotor slowing and distal extremity paraesthesias are less common in children than in adults. [236,237,242,245] In addition to the above specific cognitive problems, generalized cognitive dysfunction is reported in 4-31% of children and adults.…”
Section: Cnsmentioning
confidence: 99%
“…Topiramate (TPM) is a novel antiepileptic drug that has been used successfully, either as a single or an adjunctive therapy, to control both partial and generalized epileptic seizures in pediatric patients [10][11][12][13]. Few preliminary studies report favorable cognitive and/or QOL changes with TPM [14,15] but these effects have not been well documented in children.…”
Section: Introductionmentioning
confidence: 99%
“…Bruni et al (33) assessed the efficacy of vigabatrin as add-on therapy in patients with refractory partial epilepsy and found that it was well tolerated by 7.2% of patients receiving the drug. Topiramate use is more sustained in localization related epilepsy than in generalized epilepsy (34). It can be used as adjunctive therapy in children, adolescents and young adults with Lennox Gastaut syndrome (35).…”
Section: Efficacy Of New Versus Old Aedsmentioning
confidence: 99%